Incidence of sarcopenia and physical disability in elderly patients in nursing practice - Doležalová, Jitka; Neugebauer, Jan; Tóthová, Valérie (Journal of Nursing, Social Studies and Public Health, 2021)
Background: An overview of sarcopenia status assessment using assessment tools and other measurement techniques over the last 3 years. Purpose: The main goal of the study is to survey the practical information on the incidence of sarcopenia and physical disability in the elderly population, and to analyze the available sarcopenia measurements in nursing practice. Methods: Based on the determined conditions, 9 studies were selected that focus on the evaluation of sarcopenia. Results: The results show that the evaluation criteria according to EWGSOP are the most frequently used for the diagnosis of sarcopenia. Based on the analysis of these studies, SARC.F became the most widely used assessment tool. Conclusions: Sarcopenia is a serious disease that comes with age. It has been shown to cause disability in the elderly population. It is necessary to regularly treat sarcopenia and implement it more in nursing care.
Keywords: průzkumy a dotazníky; hodnocení rizik; Prevalence; Epidemiologic Methods; Surveys and Questionnaires; lidé; Activities of Daily Living; Risk Assessment; prevalence; činnosti denního života; postižení; Aged; Nursing Assessment; epidemiologické metody; Persons with Disabilities; senioři; ošetřovatelské zhodnocení; sarkopenie; Sarcopenia; Humans